Time Constraints of Late Cenozoic Tectonic Deformation of the Atushi Anticline, Southwestern Tian Shan: Evidence From Cosmogenic Nuclide Burial Age - Chen, Qingyu; Fu, Bihong; Shi, Pilong; Kong, Ping (Frontiers in Earth Science, 2022)
With the latest uplift episode of Tian Shan occurred since Miocene, foreland basins on both sides of Tian Shan continuous expanding, a series of thrust-fold belts were formed in the front of Tian Shan. The Kashi foreland thrust-fold belt (KFTB) provided a unique case to understand intracontinental ongoing deformation within the Pamir-Tian Shan convergence zone (PTCZ). Previous cosmogenic nuclide chronological study on growing folds in the front of Pamir suggested that the young thrust-fold belt formed during 6~1.07 Ma. However, age constraints of late Cenozoic deformation in the front of southwestern Tian Shan is still debated. In this study, we attempt to constrain the formation time of the NEE-striking Atushi anticline (ATA) in KFTB through the cosmogenic nuclide burial dating data of the Pliocene-Pleistocene Atushi Formation (N2a) and Xiyu Formation (Q1x), which developed in the southern limb of ATA. Moreover, the detailed interpretations of multiple remote sensing images and field investigations are also carried out to understand late Cenozoic structural deformation and geomorphologic features. The 26Al/10Be burial dating data of four fine-grained samples, collected from the Pliocene-Pleistocene sedimentary strata near the boundary between N2a and Q1x, indicated that syntectonic deposit of ATA initiated at 1.79±0.16 Ma (the upper part of N2a), and the deposit of Q1x started since 1.67±0.18 Ma. Finally, we suggest that the thrust-folding of ATA began at ca.1.79 Ma and is currently still active.